Az ágytól és asztaltól történő elválasztás az egyházjogban a 19-20. században, kitekintéssel a magyar magánjogra - Tamási, Anna Éva (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The most important procedure before canonical tribunals was separation from bed and board (separatio a mensa et toro) which has been the most frequent procedure and has been the antecedent of the divorce trial. (Although it has to be mentioned that the latter has not been a ‘classical’ divorce, because it was not permitted for a long time, more exactly until the Marriage Act of 1894.) Moreover, it could be mentioned that the matrimonial regulation of the two legal systems, namely the national particular canon law and the State private law, has been strongly influenced by each other which was reflected in the interacted legal institutions such as in the regulation of the separation.